Intestinal knotting : A case report and brief literature review - Sohail, Mushtaq; Tan, Alyson Su Yin; Sim, Sze Kiat; Nik Azim, Nik Abdullah (Malaysian Medical Association, 2020)
Ileo-ileal knotting is a rare cause of intestinal obstruction. In this condition, one bowel loop makes a knot with an adjacent bowel loop, resulting in mechanical obstruction and even gangrene of the bowel. We present a case of a young girl with ileo-ileal knotting resulting in a closed-loop obstruction and gangrene of the small bowel loop. This is a difficult condition to diagnose; a high index of suspicion and early surgical intervention are essential to reduce morbidity and mortality.